Case Report: Anaphylaxis caused by traditional Chinese medicine in a patient with pollinosis - Pan, Zhouxian; Zhan, Mengyuan; Wang, Qing; Liu, Jun; Li, Yu; Zhi, Fan; Zhang, Jing; Liu, Jinhe; Guan, Kai; Wen, Liping (Frontiers in Allergy, 2024)
This case describes a patient with anaphylaxis caused by traditional Chinese medicine. Skin prick test with the traditional Chinese medicine decoction indicates that he was allergic to Suan Zao Ren. The patient had pollinosis and had never taken Suan Zao Ren before, thus we need to think the possibility of pollen food allergy syndrome. This paper also proposes a procedure for doctors to identify the specific culprit of traditional Chinese medicine decoction.